Cell-in-Cell Events in Oral Squamous Cell Carcinoma - Siquara da Rocha, Leonardo de Oliveira; Souza, Bruno Solano de Freitas; Lambert, Daniel W.; Gurgel Rocha, Clarissa de Araújo (Frontiers in Oncology, 2022)
For over a century, cells within other cells have been detected by pathologists as common histopathological findings in tumors, being generally identified as “cell-in-cell” structures. Despite their characteristic morphology, these structures can originate from various processes, such as cannibalism, entosis and emperipolesis. However, only in the last few decades has more attention been given to these events due to their importance in tumor development. In cancers such as oral squamous cell carcinoma, cell-in-cell events have been linked to aggressiveness, metastasis, and therapeutic resistance. This review aims to summarize relevant information about the occurrence of various cell-in-cell phenomena in the context of oral squamous cell carcinoma, addressing their causes and consequences in cancer. The lack of a standard terminology in diagnosing these events makes it difficult to classify the existing cases and to map the behavior and impacts of these structures. Despite being frequently reported in oral squamous cell carcinoma and other cancers, their impacts on carcinogenesis aren’t fully understood. Cell-in-cell formation is seen as a survival mechanism in the face of a lack of nutritional availability, an acid microenvironment and potential harm from immune cell defense. In this deadly form of competition, cells that engulf other cells establish themselves as winners, taking over as the predominant and more malignant cell population. Understanding the link between these structures and more aggressive behavior in oral squamous cell carcinoma is of paramount importance for their incorporation as part of a therapeutic strategy.